PENGEMBANGAN KEPRIBADIAN MUSLIM PADA ANAK TINGKAT SEKOLAH DASAR - Muhaemin, Ujang (Lembaga P3M, 2021)
This article discusses the development of Muslim personality in children at the elementary school level. The method used is the method of literature and content analysis. In this case the writer collects data from various written sources and then performs the analysis. The development of the Muslim personality is an effort made by the individual consciously to maximize his human potentials, so that he is able to properly realize and actualize the five pillars of Islam so that he becomes a person who is rahmatan li al-'lam?n who obtains a quality of life in the world and in the hereafter. The development of Muslim personality for elementary school level students is: coaching, education and training both formal and non-formal which are carried out consciously, planned, directed, regularly and responsibly in order to introduce, cultivate, guide and develop their nature so that they have a complete and complete Muslim personality. balanced, whether related to taste, creativity or commitment by being based on Islamic teachings, especially the pillars of Islam.